Cardiovascular autonomic modulation differences between moderate-intensity continuous and high-intensity interval aerobic training in women with PCOS: A randomized trial - Philbois, Stella V.; Ribeiro, Victor B.; Tank, Jens; Reis, Rosana Maria dos; Gerlach, Darius A.; Souza, Hugo C. D. (Frontiers in Endocrinology, 2022)
Background: Moderate-intensity continuous training (MICT) is strongly recommended for polycystic ovarian syndrome (PCOS) treatment. However, recent studies have suggested that high-intensity interval training (HIIT) would promote great benefits for cardiac autonomic control. Therefore, we investigated whether the benefits of HIIT related to cardiovascular autonomic control were greater than those of MICT in women with PCOS. Methods: Women with PCOS were randomly allocated through a blind draw into three groups: control, MICT, and HIIT. The control group did not undergo exercise, whereas those in the MICT and HIIT groups underwent 16 weeks of aerobic physical training. All groups were evaluated before and after the 16 weeks of intervention in the following aspects: quantification of serum lipids, testosterone, fasting insulin and blood glucose; physical fitness through cardiopulmonary testing; analysis of heart rate variability (HRV) by linear (time domain and frequency domain) and non-linear (symbolic analysis) methods, analysis of blood pressure variability (BPV) and spontaneous baroreflex sensitivity (BRS). Results: The final analysis, each group comprised 25 individuals. All groups had similar baseline parameters. After 16 weeks, intragroup comparison showed that the MICT and HIIT groups had a reduction in baseline heart rate (P < 0.001; P < 0.001, respectively) and testosterone levels P < 0.037; P < 0.012, respectively) associated with an increase in VO2peak (MICT, P < 0.001; HIIT, P < 0.001). The HIIT group also showed an increase in cardiac vagal modulation, however only observed in the non-linear analysis. The intergroup comparison showed no differences between the MICT and HIIT groups in any of the hormonal, metabolic and autonomic parameters evaluated, including testosterone, peak oxygen uptake (VO2peak), HRV, BPV and BRS. Conclusion: HIIT and MICT showed similar results for the different parameters evaluated. This suggests that both training protocols can be recommended for the treatment of PCOS. Brazilian Clinical Trials Registry (RBR-78qtwy).